Public Administration The Essentials - Renfro, Jayme L. (Open textbook library., 2023)
Public Administration: The Essentials provides students with the conceptual foundation they need for an introduction to the field of public administration. This OER textbook covers the most critical issues in the field through the use of classic texts and theory as well as through modern examples.